+0  
 
+3
354
2
avatar

$${\frac{{\mathtt{dy}}}{{\mathtt{dx}}}}$$ of $${\mathtt{y}}{\mathtt{\,\small\textbf+\,}}{{\mathtt{e}}}^{{\mathtt{y}}} = {{\mathtt{x}}}^{{\mathtt{2}}}$$

andf(x)= $${{\mathtt{sinxcos}}}^{{\mathtt{3}}}$$X in to f'(x)

Guest Sep 18, 2014

Best Answer 

 #2
avatar+26716 
+8

y + ey = x2

Differentiating this with respect to x we get:

dy/dx + ey*dy/dx = 2x   (Use the chain rule for dey/dx: i.e.  dey/dy*dy/dx)

(1 + ey)*dy/dx = 2x

dy/dx = 2x/(1 + ey)

 

f(x) = sin(x)*cos3(x) 

df(x)/dx = sin(x)*dcos3(x)/dx + cos3(x)*dsin(x)/dx

df(x)/dx = sin(x)*3cos2(x)*(-sin(x)) + cos3(x)*cos(x)

df(x)/dx = cos2(x)*(-3sin2(x) + cos2(x))

Now since cos(2x) = cos2(x) - sin2(x) = 1 - 2sin2(x) = 2cos2(x) - 1 we could write

df(x)/dx = (cos(2x) + 1)*(2cos(2x) - 1)/2

Alan  Sep 18, 2014
 #2
avatar+26716 
+8
Best Answer

y + ey = x2

Differentiating this with respect to x we get:

dy/dx + ey*dy/dx = 2x   (Use the chain rule for dey/dx: i.e.  dey/dy*dy/dx)

(1 + ey)*dy/dx = 2x

dy/dx = 2x/(1 + ey)

 

f(x) = sin(x)*cos3(x) 

df(x)/dx = sin(x)*dcos3(x)/dx + cos3(x)*dsin(x)/dx

df(x)/dx = sin(x)*3cos2(x)*(-sin(x)) + cos3(x)*cos(x)

df(x)/dx = cos2(x)*(-3sin2(x) + cos2(x))

Now since cos(2x) = cos2(x) - sin2(x) = 1 - 2sin2(x) = 2cos2(x) - 1 we could write

df(x)/dx = (cos(2x) + 1)*(2cos(2x) - 1)/2

Alan  Sep 18, 2014
 #3
avatar+92623 
+3

Thanks Alan,

I was waiting for you to answer that first one.  

Melody  Sep 18, 2014

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.